1990
DOI: 10.1073/pnas.87.19.7400
|View full text |Cite
|
Sign up to set email alerts
|

mRNA coding for oxytocin is present in axons of the hypothalamo-neurohypophysial tract.

Abstract: Neuronal mRNA is thought to be restricted to perikaryal and dendritic compartments containing rough endoplasmic reticulum. We have used both in situ hybridization and DNA polymerase chain reaction methods to determine the precise intracellular distribution of oxytocin mRNA. Using light-and electron-microscopic detection of in situ hybridization with 5'-bromo-2'-deoxyuridine-labeled oligonucleotide probes, we found oxytocin mRNA in axons and Herring bodies in the lateral and ventral hypothalamus, the median emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(82 citation statements)
references
References 24 publications
4
77
0
Order By: Relevance
“…In conclusion, the discovery of NF-M mRNA within the goldfish M-axon increases the number of known axonally localized mRNAs, including oxytocin mRNA in the rat hypothalamoneurohypophyseal tract [9], caudodorsal cell hormone mRNA in the central nervous system of the mollusc Lymnea stagnalis [5], kinesin mRNA in the squid giant axon [6], and arginine vasopressin precursor mRNA in rat hypothalamo magnocellular neurons [19]. The presence of mRNA in the M-axon is particularly significant given previous reports of tRNA, rRNA, polyribosomes, and protein synthesis in the M-axon [13][14][15].…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In conclusion, the discovery of NF-M mRNA within the goldfish M-axon increases the number of known axonally localized mRNAs, including oxytocin mRNA in the rat hypothalamoneurohypophyseal tract [9], caudodorsal cell hormone mRNA in the central nervous system of the mollusc Lymnea stagnalis [5], kinesin mRNA in the squid giant axon [6], and arginine vasopressin precursor mRNA in rat hypothalamo magnocellular neurons [19]. The presence of mRNA in the M-axon is particularly significant given previous reports of tRNA, rRNA, polyribosomes, and protein synthesis in the M-axon [13][14][15].…”
mentioning
confidence: 84%
“…The M-axon is a particularly advantageous preparation because more basic components of the translational machinery (transfer RNA (tRNA), ribosomal RNA (rRNA), and ribosomes) have been identified in the M-axon [13][14][15] compared to any other vertebrate axon. However, no direct evidence has been published for any mRNAs that could function as templates for protein synthesis in M-axoplasm, although mRNAs have been reported in other vertebrate axons [9,19] for which the presence of translational machinery …”
mentioning
confidence: 99%
“…Although axons do not contain ribosomes, they do contain many mRNAs (Perrone-Capano et al, 1987). Some mRNA species have been identified that appear to be specifically targeted to axons, including those for ␤-actin (Olink-Coux and Hollenbeck, 1996), vasopressin (Trembleau et al, 1994;Mohr et al, 1995), oxytocin (Jirikowski et al, 1990), and BC1 (Tiedge et al, 1993). The lack of axonal ribosomes has led to an assumption that translation does not occur in axons, however, some evidence for axonal protein synthesis is beginning to accumulate (reviewed in Van Minnen, 1994).…”
Section: Fmrp In Dendritic and Axonal Compartmentsmentioning
confidence: 99%
“…The lack of axonal ribosomes has led to an assumption that translation does not occur in axons, however, some evidence for axonal protein synthesis is beginning to accumulate (reviewed in Van Minnen, 1994). It has also been hypothesized that axonal targeting of mRNA down-regulates protein synthesis by removing these mRNAs from the translating ribosomes (Jirikowski et al, 1990;Mohr et al, 1995). Whether FMRP has any functional significance in the axon still remains to be elucidated; however, it may play a role in the localization or regulation of some axonal mRNAs.…”
Section: Fmrp In Dendritic and Axonal Compartmentsmentioning
confidence: 99%
“…Interestingly, this is accompanied by an elongation of their poly(A) tails although the physiological significance remains to be determined [4][5][6]. Both AVP and OT mRNAs are subject to axonal targeting [7][8][9] and hyperosmolar stimuli give rise to a differential increase in the level of AVP (17-fold) and OT (3-fold) mRNAs in the axonal compartment [8,[10][11][12]. The axonal transcripts exhibit shorter poly(A) tracts than their counterparts in the cell bodies [2], and a poly(A) tail polymorphism following osmotic challenge is not observed for these transcripts [12].…”
Section: Introductionmentioning
confidence: 99%